2014
DOI: 10.1111/hel.12146
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Helicobacter pylori Eradication on Metachronous Gastric Cancer after Endoscopic Resection of Gastric Tumors: A Meta‐Analysis

Abstract: Helicobacter pylori eradication reduces the occurrence of metachronous gastric cancer in patients who have undergone endoscopic resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
86
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(94 citation statements)
references
References 45 publications
(80 reference statements)
5
86
0
3
Order By: Relevance
“…Th e most inclusive analysis by Yoon et al ( 33 ) included 13 studies (three prospective and 10 retrospective) comprising 6687 patients. Th e pooled OR of gastric cancer in patients successfully cured of H. pylori was 0.42 (95% CI 0.32-0.56); in a subgroup analysis of the three prospective studies, the OR was 0.39 (95% CI 0.20-0.75) ( 33,34 ). Th e other two meta-analyses yielded similar results ( 31,32 ).…”
Section: Early Gastric Cancermentioning
confidence: 69%
See 1 more Smart Citation
“…Th e most inclusive analysis by Yoon et al ( 33 ) included 13 studies (three prospective and 10 retrospective) comprising 6687 patients. Th e pooled OR of gastric cancer in patients successfully cured of H. pylori was 0.42 (95% CI 0.32-0.56); in a subgroup analysis of the three prospective studies, the OR was 0.39 (95% CI 0.20-0.75) ( 33,34 ). Th e other two meta-analyses yielded similar results ( 31,32 ).…”
Section: Early Gastric Cancermentioning
confidence: 69%
“…Th ree recent meta-analyses have each found that the incidence of metachronous gastric cancer following the endoscopic resection of a gastric neoplasm was reduced by the eradication of H. pylori infection (31)(32)(33). Th e most inclusive analysis by Yoon et al ( 33 ) included 13 studies (three prospective and 10 retrospective) comprising 6687 patients.…”
Section: Early Gastric Cancermentioning
confidence: 99%
“…The incidence of AG decreased from 59.9 to 13.7 %, while the incidence of both IM and DYS increased from 40.1 to 56.1 % [14]. On the other hand, in patients without history of GC, several reports have shown the close correlation between H. pylori infection and metachronous GC occurrence [21,[25][26][27], however, most of them also emphasized that limited effect of eradication therapy in prevention of metachronous GC, especially in patients with IM nor DYS [28].Therefore, we believed that overall reduction of GC incidence is mainly due to the retaining of progression in patients with baseline diagnosis \IM, and malignancy transformation could hardly be prevented in those with IM or DYS. Prospective studies, especially RCTs, which regarded the occurrence of GC as primary outcome were few, because the gastric carcinogenesis was time-consuming process which need long-term follow-up.…”
Section: Discussionmentioning
confidence: 95%
“…Thus, we still considered the occurrence of metachronous GC as part of our analysis. Although these conclusion have been supported by several meta-analyses [21], the controversies still exist regarding whether H. pylori eradication would be sufficient to prevent GC. For example, even with a similar research design, opposite conclusions were still drawn from these RCTs [6,10,19].…”
Section: Discussionmentioning
confidence: 99%
“…Although there is a close relationship between H. pylori infection and gastric cancer, the effectiveness of eradicating the bacteria in preventing gastric cancer remains controversial [8,9,10]. There have been some reports of metachronous gastric cancer development after the eradication of H. pylori [11,12,13]. In addition, some studies have investigated changes in the health of the gastric mucosa, such as the severities of atrophic gastritis and intestinal metaplasia, after H. pylori eradication [14,15,16,17].…”
Section: Introductionmentioning
confidence: 99%